On the thesis of the claim to correctness in Robert Alexy: some critical considerations - García Amado, Juan Antonio (EUNOMÍA. Revista en Cultura de la Legalidad, 2014)
In this essay, the author criticizes Robert Alexy’s thesis that there is a claim to correctness in legal discourse, which makes the law a special case of practical discourse and creates a legal duty to decide juristic cases in a morally correct way. Firstly, it is argued that Alexy is wrong to assume that positivism implies judicial discretion to decide according to irrational and randomly chosen criteria, since it is perfectly possible – and even recommendable, in the face of the principle of motivation of judicial decisions – for a positivist judge to deploy moral arguments to fill in the gaps derived from the inexistence of a specific solution for a given legal issue. Secondly, the paper argues that Alexy’s thesis that an express recognition of the injustice of a legal norm would amount to a performative contradiction is circular and cannot be accepted, since a judge only would commit such contradiction if he already accepted a concept of law according to which a certain level of justice is a necessary condition for the validity of a legal provision. Thirdly, the essay attempts to demonstrate with concrete examples that even if this circularity could be overcome, the thesis of the claim to correctness should be rejected because it is an inconvenient, enigmatic and useless theoretical trick. Alexy fails, therefore, to ground both the thesis that there is a legal duty to decide in a morally correct way and the thesis that legal discourse is a special case of practical discourse.